The Use of a Non-Absorbable Membrane as an Occlusive Barrier for Alveolar Ridge Preservation: A One Year Follow-Up Prospective Cohort Study - Piero Papi; Bianca Di Murro; Marco Tromba; Pier Carmine Passarelli; Antonio D'Addona; Giorgio Pompa (MDPI AG, 2020)
：The aims of this study were to obtain preliminary data and test the clinical efficacy of a novel nonporous dense-polytetrafluoroethylene (d-PTFE) membrane (permamem®, botiss) in alveolar ridge preservation (ARP) procedures with a flapless approach. A traumatic extraction was performed in the premolar maxillary area, and a d-PTFE membrane was used to seal the alveolar cavity: no biomaterial was used to graft the socket and the membrane was left intentionally exposed and stabilized with sutures. The membrane was removed after four weeks and dental implants were placed four months after the procedure. The primary outcome variables were defined as the dimensional changes in the ridge width and height after four months. A total of 15 patients were enrolled in this study. The mean width of the alveolar cavity was 8.9 ± 1.1 mm immediately after tooth extraction, while four months later a mean reduction of 1.75 mm was experienced. A mean vertical reduction of 0.9 ± 0.42 mm on the buccal aspect and 0.6 ± 0.23 mm on the palatal aspect were recorded at implant placement. Within the limitations of this study, the d-PTFE membrane proved to be effective in alveolar ridge preservation, with the outcomes of the regeneration not affected by the complete exposure of this biomaterial.